Arsenic removal from aqueous solutions by diethylenetriamine-functionalized resin: isotherm, kinetics, selectivity and mechanism. Issue 9 (12th September 2018) - Zhang, Juncai; Chen, Youning; Zhao, Wei; Li, Yuhong
Abstract : The surface-initiated atom transfer radical polymerization method was used to graft glycidyl methacrylate (GMA) on chloromethylated cross-linked styrene-divinylbenzene resin, and then the novel diethylenetriamine-functionalized resin was prepared through the amination reaction between amino group of diethylenetriamine and epoxy group in GMA. The adsorption properties were evaluated with As(V). The adsorption of As(V) was mainly regarded as the electrostatic interaction between the adsorbent and the adsorbate by analysing the relationship between adsorption capacity with the solution pH, adsorption isotherm and adsorption kinetics. The maximum sorption capacity of As(V) was 5.25 mmol g −1 . The adsorption isotherms of As(V) were best described by the Langmuir model, and its adsorption kinetics followed the pseudo-second-order kinetic equation. The adsorption of As(V) ions was hardly affected by common coexisting ions such as Na(I), K(I), Ca(II) and Mg(II), whereas it was slightly decreased when Fe(II) and Zn(II) coexisted in the solution, which illustrates the selective adsorption of As(V) from wastewater. Ten adsorption–desorption cycles demonstrated that the resin possessed high recycling efficiency and stability and was suitable for efficient removal of metal ions from aqueous solution.